Winter Wheat Variety-Specific Response to the Combination of Nitrogen and Foliar Fungicide in 2018–2019 - R. P. Lollato; K. Mark; B. R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2020)
Yield improvements to wheat can result both from variety selection and adoption of improved management practices. However, the yield response to improved management practices can be variety-specific and can result in decreases in protein concentration. Our objectives were to evaluate the yield and protein responses of different commercial winter wheat varieties to increased nitrogen (N) rates and application of foliar fungicides. We conducted a trial combining 20 winter wheat varieties and two management level intensities. The standard management consisted of N applied for a 75 bushel per acre yield goal and no fungicide; and intensive management consisted of an additional 40 pounds of N per acre and two fungicide applications—the first at jointing and the second at flag leaf emergence. The study was conducted at two Kansas locations (Great Bend, following a terminated cover crop; and Ashland Bottoms, following a previous soybean crop) during the 2018–2019 growing season. Grain yield ranged from 18–103 bushels per acre, with greatest yields recorded in the intensive management treatment in Great Bend and the lowest yields recorded in the standard management treatment in Ashland Bottoms. While there were no statistical differences in the varieties’ responses to intensive management, both the ranking of varieties and the yield increase from intensive management depended on location. Grain protein concentration ranged from 10.5–17.7% across all treatments, and the intensive management increased grain protein concentration from 12.7–13.9% in Ashland Bottoms and from 14.1–14.5% in Great Bend. The intensive management concomitantly increased grain yield and grain protein concentration at Ashland Bottoms, and increased grain yield while sustaining grain protein concentration at Great Bend, suggesting that total N removal in the grain increased with intensive management. While we did not investigate the net profits from the intensive management, these results suggest that intensifying management on wheat could add income from additional yield produced and protein premiums, as long as these are available.
Keywords: wheat; yield gap; intensive management; variety